Economic Contributions of Agriculture, Natural Resources, and Food Industries in Florida in 2014 - Alan W. Hodges; Mohammad Rahmani (EDIS, 2016)
Agriculture, natural resources, and food industries remain a significant force in the economy of Florida, and informed public policy demands recognition of the economic contributions of these industries. Economists at the University of Florida Institute of Food and Agricultural Sciences (UF/IFAS) evaluated the economic contributions of the agriculture, natural resources, and food industries for calendar year 2014 to update previous reports and provide current information on economic trends.